1998
DOI: 10.1126/science.281.5380.1197
|View full text |Cite
|
Sign up to set email alerts
|

Prototype of a Heme Chaperone Essential for Cytochrome c Maturation

Abstract: Heme, the iron-containing cofactor essential for the activity of many enzymes, is incorporated into its target proteins by unknown mechanisms. Here, an Escherichia coli hemoprotein, CcmE, was shown to bind heme in the bacterial periplasm by way of a single covalent bond to a histidine. The heme was then released and delivered to apocytochrome c. Thus, CcmE can be viewed as a heme chaperone guiding heme to its appropriate biological partner and preventing illegitimate complex formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
241
2
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(257 citation statements)
references
References 19 publications
13
241
2
1
Order By: Relevance
“…CcmC binds haem in the periplasm, probably via two conserved histidines in the first and the third periplasmic loops, the interaction being stabilized by hydrophobic amino acids in the second periplasmic loop, mostly composed of tryptophan residues Schulz et al, 2000). It has been established that CcmC further delivers haem to another membrane protein, CcmE, considered to be a haem chaperone that passes haem to a haem lyase complex (comprising the CcmF protein) before covalent binding of the haem prosthetic group to apocytochromes c (Schulz et al, 1998(Schulz et al, , 1999(Schulz et al, , 2000. CcmC has been postulated to be a cytoplasmto-periplasm haem exporter Goldman et al, 1998) and has been demonstrated to interact with the CcmAB ABC transporter (Goldman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…CcmC binds haem in the periplasm, probably via two conserved histidines in the first and the third periplasmic loops, the interaction being stabilized by hydrophobic amino acids in the second periplasmic loop, mostly composed of tryptophan residues Schulz et al, 2000). It has been established that CcmC further delivers haem to another membrane protein, CcmE, considered to be a haem chaperone that passes haem to a haem lyase complex (comprising the CcmF protein) before covalent binding of the haem prosthetic group to apocytochromes c (Schulz et al, 1998(Schulz et al, , 1999(Schulz et al, , 2000. CcmC has been postulated to be a cytoplasmto-periplasm haem exporter Goldman et al, 1998) and has been demonstrated to interact with the CcmAB ABC transporter (Goldman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…CcmCDE are involved in heme delivery. CcmC is required for the covalent attachment of heme to the heme chaperone CcmE (10)(11)(12). CcmF has been proposed to form a bacterial cytochrome c heme lyase complex together with CcmH (13).…”
mentioning
confidence: 99%
“…1A) comprises the membrane-bound proteins CcmABCDEFGH. CcmA, CcmB, and CcmC form an ABC-type transporter, the function of which is unknown (20,21), although it is known that CcmC, together with CcmE, is involved in heme delivery to the cytochrome c heme lyase complex consisting of CcmFH (22)(23)(24)(25)(26). Reduction of the cysteinyls of the Cys-Xxx-Xxx-Cys-His motif prior to heme insertion is accomplished by CcmG and CcmH, but it is not clear whether the electrons flow from CcmG by means of CcmH, or from CcmH via CcmG, to the apo-cytochrome (27,28).…”
mentioning
confidence: 99%